Electric Vehicle Use Trends: A Systematic Literature Review of the Global Key Drivers - Hashari Kamaruddin; Gumilar Rusliwa Somantri; Mohamad Dian Revindo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the global trend of electric vehicle (EV) adoption by highlighting the urgency, implementation challenges, and supporting factors. Using a Systematic Literature Review (SLR) approach based on PRISMA guidelines, this study analyzed 58 selected articles from the Scopus and Google Scholar databases. The literature search process was conducted using a combination of keywords that reflect the urgency of EV use, inhibiting factors, and consumer decisions. Data analysis was conducted bibliometrically using VOSviewer and Publish or Perish software, resulting in the visualization of seven interconnected thematic clusters, such as climate change, charging infrastructure, incentive policies, and public perception. The results show that EV adoption is a systemic response to the environmental crisis, dependence on fossil fuels, and the need for a sustainable transportation system. Although EVs offer long-term efficiency and ecological benefits, barriers such as high initial prices, limited infrastructure, and low public literacy remain major challenges. This study provides a comprehensive understanding for formulating policy strategies and developing the EV industry in Indonesia, in line with the government's targets to reduce emissions and encourage the transition to clean energy.